Application of green hydrogen with theoretical and empirical approaches of alkaline water electrolysis: Life cycle-based techno economic and environmental assessments of renewable urea synthesis. (19th May 2023) - Kim, Heehyang; Choe, Changgwon; Lee, Aejin; Lim, Hankwon
Abstract: Alkaline water electrolysis which is the most commercialized and mature technology of water electrolysis was researched to improve performance by the Korea Institute of Energy Research (KIER). In line with the trend of energy shift, renewable urea production through hydrogen production from alkaline water electrolysis was proposed in this work. To validate the process modeling of renewable urea production and hydrogen performance analysis with I–V curves was assessed. Economic and life cycle assessments were conducted to provide quantitative guidelines for renewable urea production. Absolutely, the influential factor of unit urea production cost was hydrogen from alkaline water electrolysis and environmental assessment results as well. Moreover, the guidelines for renewable urea production were provided through cost estimation and life cycle assessment. In summary, hydrogen production from alkaline water electrolysis had a significant impact on urea production and for this reason, research on alkaline water electrolysis should continue for further development. Graphical abstract: Based on experimental results, process simulation was performed, and comprehensive analysis was conducted including economic analysis and life cycle assessment. The experimental results from Korea Institute of Energy Research (KIER). Image 1 Highlights: Comprehensive analysis was conducted for renewable urea production. Based on experimental results, process modeling was performed. Technical analysis of renewable urea production was considered with I–V curve. Economic analysis was conducted for renewable urea production. Life cycle assessment of renewable urea production was demonstrated.